Leveraging Dual Usability Methods to Evaluate Clinical Decision Support Among Patients With Traumatic Brain Injury: Mixed Methods Study - Rubina F Rizvi; Sameen Faisal; Mark Sussman; Patricia Mendlick; Sam Brown; Elizabeth Lindemann; Sean Switzer; Genevieve B Melton; Christopher J Tignanelli (JMIR Human Factors)
Abstract BackgroundPatients with traumatic brain injury are at an increased risk of developing venous thromboembolism. Clinical decision support systems (CDSSs) may improve the use of venous thromboembolism prophylaxis protocols, yet suffer from poor compliance among end users due to a lack of user-centered design. ObjectiveThe objective of this work was to improve the content, design, and workflow integration of a traumatic brain injury–CDSS based on feedback from experts and end users. MethodsThe CDSS was evaluated leveraging a dual usability approach. A set of usability experts (n=3) and trauma providers (n=5) performed heuristic evaluations and usability testing by end users. Data was collected through a triangulation of methods and analyzed using qualitative (thematic) and quantitative (descriptive) analyses. ResultsAmong the 145 total issues identified across both methods, 66 issues were found to be unique. Of the 66, a total of 17 issues were found by heuristic evaluations, 43 by usability testing by end users, and 6 were found across both methods. Thematic analysis was conducted on the 66 unique issues, which were further assigned to themes and subsequent subthemes. We identified 13 unique themes. The 3 most prevalent themes of 66 issues were lack of supporting evidence (n=17, 26%), operational barriers arising from the test environment (n=11, 17%), formatting inconsistencies, and lack of following standards (n=8, 12%). The system’s usability scale survey score was 77.5 (SD 16, 95% CI 57.6-97.4), interpreted as an acceptable or good usability range. The mean response score for Single Ease Questions for all tasks was 5.9 (SD 0.53). ConclusionsCombining expert and end user–driven usability evaluation methods identified a more comprehensive list of issues. This can facilitate the optimization of the traumatic brain injury–CDSS, resulting in improved usability and care management.